2019 American Control Conference (ACC) 2019
DOI: 10.23919/acc.2019.8814618
|View full text |Cite
|
Sign up to set email alerts
|

A Switching Nonlinear MPC Approach for Ecodriving

Abstract: In recent years many works focusing on improved vehicle fuel efficiency through advanced control have been carried out, reflecting the high interest in ecodriving of vehicles. Although many studies have shown the potential that optimal control based ecodriving can offer, these solution are often difficult to be translated into online control strategies, one of the reasons being the complexity of the optimal control problem and therefore the computational burden.To cope with this a novel online approach, based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…In particular, the value N b plays a crucial role and, after a sensitivity study, the most significant choices for field implementations are indicated. Clearly, as expected, the computation time rises with Table III: Dependency of computation time on the parameters N b and N p with weights µ t f = 0.005, µ gs = 0.00022, [34]. both higher N p and N b .…”
Section: A Performance Of the Proposed Snmpcsupporting
confidence: 67%
See 3 more Smart Citations
“…In particular, the value N b plays a crucial role and, after a sensitivity study, the most significant choices for field implementations are indicated. Clearly, as expected, the computation time rises with Table III: Dependency of computation time on the parameters N b and N p with weights µ t f = 0.005, µ gs = 0.00022, [34]. both higher N p and N b .…”
Section: A Performance Of the Proposed Snmpcsupporting
confidence: 67%
“…As for the impact of the restriction to modes, the performance of the proposed SNMPC accounting emissions is comparable to that in [34], with Pareto fronts in terms of t f and m fuel closer to the optimal ones achieved via EDPm, higher the horizon is. The discretization parameters used to solve the optimal control problem through EDPm are given in Table II.…”
Section: A Performance Of the Proposed Snmpcmentioning
confidence: 90%
See 2 more Smart Citations
“…Among many works in the literature, in [10], [11], for instance, a switching formulation of the eco-driving control problem is adopted and a switched nonlinear Model Predictive Control is designed to solve the problem in presence of velocity, acceleration, emission and fuel consumption constraints. The minimization of the idle time is discussed in [12] together with emission and acceleration/deceleration limits.…”
Section: Introductionmentioning
confidence: 99%